Optimisation of Biochar Addition in Anaerobic Digestion of Cow Manure to Improve Biogas Quality - Kinia Eldwita; Leila Kalsum; Aida Syarif (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The demand for sustainable alternative energy is rising due to fossil fuel depletion and environmental concerns. Anaerobic digestion (AD) of organic waste, such as cow manure, offers a promising solution by generating renewable biogas, managing waste, and mitigating greenhouse gas emissions. However, AD performance is frequently limited by process instability, the accumulation of inhibitory compounds like volatile fatty acids and ammonia, and the slow growth of methanogens. Biochar is a promising additive in AD systems because it can act as a microbial support medium, adsorb inhibitors, stabilize pH, and facilitate electron transfer, ultimately boosting methane production. This study provides a comparative evaluation of rice husk and palm kernel shell biochar under identical AD conditions to identify the optimal biochar type and dosage for methane enhancement. Biochar was applied at dosages of 5, 10, and 15 g/L. Substrate characteristics were analysed using COD, total nitrogen, TSS, and VSS, while biochar properties were characterized using SEM–EDX and BET. Biogas composition was determined by gas chromatography. Cow manure showed high suitability as substrate, with a COD of 53,333 mg/L and a VSS/TSS ratio of 94.32%. Biochar addition significantly improved methane concentration and process stability. Palm kernel shell biochar achieved the highest early methane content of 68.08% on day 15 at 5 g/L, indicating faster start-up performance. Rice husk biochar showed superior long-term stability, reaching 68.65% CH4 on day 20 at 15 g/L. These findings demonstrate that biomass-derived biochar is an effective additive for improving biogas quality and anaerobic digestion performance. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 12: Responsible Consumption and ProductionSDG 13: Climate Action